2022
DOI: 10.2147/idr.s349019
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice (KAP) Assessment on LifeStyle, Public Health Measures Practiced by Society and Their Impact to Contain COVID-19 Transmission Among Afar Community in Selected Parts of Afar Region, Ethiopia

Abstract: Introduction Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus, RNA family. It has continued to spread across the world after its first outbreak in China in 2019. On 11 March 2020 the WHO declared COVID-19 a pandemic given its global public health and economic impacts. Objective To assess knowledge, attitude and practice (KAP) on lifestyle, public health measures practiced by society and their impact to contain COVID-19 transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Besides, this study demonstrated that educational level, which is generally considered related to knowledge, is an influential factor in the intention. Furthermore, knowledge has been extensively thought of as a critical component in the fight against COVID-19, 37 as individuals with high levels of knowledge are more likely to have protective motivation. 38,39 This study was the first investigation into the acceptance of RAST among the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, this study demonstrated that educational level, which is generally considered related to knowledge, is an influential factor in the intention. Furthermore, knowledge has been extensively thought of as a critical component in the fight against COVID-19, 37 as individuals with high levels of knowledge are more likely to have protective motivation. 38,39 This study was the first investigation into the acceptance of RAST among the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…This will prevent citizens from being misled by misinformation. Additionally, another study conducted in Ethiopia showed that public information is primarily obtained through television and radio (72.6%) ( 54 ). During such tough times, it is still necessary to assist the underprivileged population who lack access to information on official online platforms due to the lack of basic infrastructure.…”
Section: Discussionmentioning
confidence: 99%